An Annotated List of the Lichens and Lichenicolous Fungi of the “Elanetsky step” Nature Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The list of the lichens and lichenicolous fungi of the “Elanetsky step ” Nature Reserve includes 163 species which belong to 66 genera, 23 families, 8 orders and group of Anamorphic fungi. 49 species of lichens and 8 species of lichenicolous fungi are revealed to be new for reserve. Data about ecology and frequency occurrence of the lichen forming and lichenicolous fungi are provided.
Keywords: lichens, lichenicolous fungi, “Elanetsky step” Nature Reserve.